Mothers' perceptions and experiences of using maternal health-care services in Rwanda. Issue 1 (2nd January 2019) - Tuyisenge, Germaine; Hategeka, Celestin; Kasine, Yvone; Luginaah, Isaac; Cechetto, David; Rulisa, Stephen
ABSTRACT: Reducing barriers to use maternal health care is one of the critical components to improving maternal health. Rwanda is among the countries that have made tremendous efforts to reduce maternal mortality. However, the current maternal mortality ratio is still high which calls for further efforts to be considered. This study used a qualitative approach to understand mothers' perceptions and experiences of using maternal health care in Rwanda. Using in-depth interviews and focus group discussions, data were collected in the Western and Eastern provinces of the country where forty-five women participated in the study from June to August 2014. This paper highlights perceptions of these participants regarding issues that contribute to suboptimal use of maternal health-care services. The geographical, financial, and social–cultural barriers that emerged in this study highlight the need to understand mothers' experiences and perceptions when using maternal health care as Rwanda and other countries strive to reduce negative maternal health outcomes.